Designing workable mobile broadband policies - Hsin-yi Sandy Tsai; Johannes M. Bauer (International Telecommunications Society (ITS), 2015)
The importance of accessing the Internet anywhere anytime has been high on the agenda of policy makers and businesses. Despite this awareness of the importance of mobile broadband access, there continue to be significant differences in mobile broadband adoption and uses among countries. Although many studies have examined the factors affecting broadband penetration rates, few studies thus far have focused on mobile broadband. Consequently, reasons for the gap on mobile broadband penetration rates among countries and potential remedies to address them remain muddy. This paper uses Qualitative Comparative Analysis (QCA) to systematically examine factors related to mobile broadband penetration. Policies and other economic and social factors usually interact with each other. OCA allows a systematic examination of the complexity of various combinations of policy and economic factors. This allows a deeper understanding of necessary and/or sufficient conditions for higher mobile broadband (high speed mobile Internet) penetration rates. The results reveal the complexity of the interaction of various conditions for mobile broadband penetration. The findings suggest that there are multiple paths toward high mobile broadband penetration, each depending on the context of institutional and non-institutional factors. An appropriate combination of spectrum policy, market access conditions, and supplementary policies to support access to disadvantaged regions and groups remains critical and has noticeable effects on sector outcomes.
Keywords: 330; QCA (Qualitative Comparative Analysis); broadband penetration; adoption